2014
DOI: 10.1364/oe.22.028653
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancement of second harmonic generation by engineering double plasmonic resonances at nanoscale

Abstract: We have investigated second harmonic generation (SHG) from Ag-coated LiNbO 3 (LN) core-shell nanocuboids and found that giant SHG can occur via deliberately designed double plasmonic resonances. By controlling the aspect ratio, we can tune fundamental wave (FW) and SHG signal to match the longitudinal and transverse plasmonic modes simultaneously, and achieve giant enhancement of SHG by 3×10 5 in comparison to a bare LN nanocuboid and by about one order of magnitude to the case adopting only single plasmonic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The strategy of getting a qualitative increase of SHG from centrosymmetric metals by designing nanostructures of asymmetric geometrical shapes was identified . It was found that in order to make it efficient, the SHG engineering should rely on a certain selection rule, expressed in a semi‐empirical criterion as 0trueE2-0.16em-0.16em-0.16emχ()2,surfE1,mode2E2,modenormaldS,where E 2 is the SHG field, χfalse(2false),surf is the surface nonlinear susceptibility tensor component, considered to be the dominant SHG source, E1,mode and E2,mode are the components of the fields perpendicular to the metal‐dielectric boundary for the modes at the fundamental and SH frequencies, respectively, and the integration is performed over the nanostructure surface. Particularly, this approach was used to optimise SHG from multiresonant coupled nanoantennas (Figure c) .…”
Section: Harmonic Generation In Plasmonic Nanostructures: Perturbativmentioning
confidence: 99%
“…The strategy of getting a qualitative increase of SHG from centrosymmetric metals by designing nanostructures of asymmetric geometrical shapes was identified . It was found that in order to make it efficient, the SHG engineering should rely on a certain selection rule, expressed in a semi‐empirical criterion as 0trueE2-0.16em-0.16em-0.16emχ()2,surfE1,mode2E2,modenormaldS,where E 2 is the SHG field, χfalse(2false),surf is the surface nonlinear susceptibility tensor component, considered to be the dominant SHG source, E1,mode and E2,mode are the components of the fields perpendicular to the metal‐dielectric boundary for the modes at the fundamental and SH frequencies, respectively, and the integration is performed over the nanostructure surface. Particularly, this approach was used to optimise SHG from multiresonant coupled nanoantennas (Figure c) .…”
Section: Harmonic Generation In Plasmonic Nanostructures: Perturbativmentioning
confidence: 99%
“…Usually, the excitation of LSPRs results in hot spots featuring locally enhanced electromagnetic field in close vicinity to photon-excited nanostructures [21]. Engineering hybrid nanostructures that combine plasmonic nanostructures with materials with large second-order susceptibility gives an opportunity to realize the effective integration of strongly enhanced and independently tunable resonances and intense sources of SH polarization [18,22,23,24]. Particular interest lies in the fact that PESHG can be achieved due to the stimulated excitation of hot spots depending on the excitation and emission energies.…”
Section: Introductionmentioning
confidence: 99%
“…Employing Fano or magnetic plasmon resonances to avoid scattering and nonradiative losses at fundamental frequency has been proved as an efficient way to enhance SHG 20 23 . Moreover, when two plasmonic resonance modes are properly matched to both the fundamental and SH frequencies, the SH emission can be further enhanced 16 , 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%